“Relief” and “Mountains”: Primary School Teachers Confronted with Discursive and Visual Framing of Salience - Alexandra Baudinault (Revue de Géographie Alpine)
In this paper my goal is to indicate how children’s geographies of the alpine mountain resonate with academic knowledge about the mountain. The aim is to show how teachers of primary school students (aged 6 to 11) use the words “relief” and “mountain”. How do they explain and show salience to their students, who perceive the mountain only through mediation in the form of pictures, illustrations, drawings or movies? What kind of discourses regarding the mountain do they develop, and how do these discourses contribute to building a cultural and spatial reality? This paper is based on an analysis of school textbooks (from the 1970s to the present day), classroom observations and digital resources created and used by teachers.